Implementation of a novel three-tier triage tool in Papua New Guinea: A model for resource-limited emergency departments (2020)
In emergency departments (EDs), demand for care often exceeds the available resources. Triage addresses this problem by sorting patients into categories of urgency. The Interagency Integrated Triage Tool (IITT) is a novel triage system designed for resource-limited emergency care (EC) settings. The system was piloted by two EDs in Papua New Guinea as part of an EC capacity development program. Implementation involved a five-hour teaching program for all ED staff, complemented by training resources including flowcharts and reference guides. Clinical redesign helped optimise flow and infrastructure, and development of simple electronic registries enabled data collection. Local champions were identified, and experienced EC clinicians from Australia acted as mentors during system roll-out. Evaluation data suggests the IITT, and the associated change management process, have high levels of acceptance amongst staff. Subject to validation, the IITT may be relevant to other resource-limited EC settings.